2004
DOI: 10.1021/pr049921p
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Human Serum by Two-Dimensional Differential Gel Electrophoresis after Depletion of High-Abundant Proteins

Abstract: Two-dimensional differential gel electrophoresis (2-D DIGE) was used to analyze human serum following the removal of albumin and five other high-abundant serum proteins. After protein removal, serum was analyzed by SDS-PAGE as a preliminary screen, and significant differences between four high-abundant protein removal methods were observed. Antibody-based albumin removal and high-abundant protein removal methods were found to be efficient and specific. To further characterize serum after protein removal, 2-D D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
148
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(165 citation statements)
references
References 32 publications
(49 reference statements)
13
148
0
2
Order By: Relevance
“…We used a columnbased multiple immunoaffinity system to remove six proteins (albumin, IgG, ␣ 1 -antitrypsin, IgA, transferrin, and haptoglobin) from human CSF. This depletion technique has been shown in a proteomic study on serum to be superior to three other similar depletion methods and resulted in a 76% increase in the number of protein spots detected (30). When loading the same amount of total protein, our CSF study showed a 99% increase in the number of spots detected ( Fig.…”
Section: Within-gel Analyses: Intraindividual Variations-becausesupporting
confidence: 50%
“…We used a columnbased multiple immunoaffinity system to remove six proteins (albumin, IgG, ␣ 1 -antitrypsin, IgA, transferrin, and haptoglobin) from human CSF. This depletion technique has been shown in a proteomic study on serum to be superior to three other similar depletion methods and resulted in a 76% increase in the number of protein spots detected (30). When loading the same amount of total protein, our CSF study showed a 99% increase in the number of spots detected ( Fig.…”
Section: Within-gel Analyses: Intraindividual Variations-becausesupporting
confidence: 50%
“…1). Recent papers have also confirmed the marked increase in detectable proteins due to immunodepletion [8,9]. Western blot analysis of raw and immunodepleted serum using an antibody to albumin also shows the effectiveness of the immuno-depletion column (Fig.…”
Section: Immunodepletion Of High-abundant Serum Proteinsmentioning
confidence: 64%
“…In this study, we build on this approach by coupling multi-component immunoaffinity subtraction with N-glycopeptide enrichment for comprehensive 2-D LC-MS/MS analysis of the human plasma N-glycoproteome. A conservatively estimated dynamic range of detection of >10 8 was achieved by effectively reducing the protein concentration range and overall sample complexity. This overall dynamic range of detection enabled confident identification of 303 non-redundant N-glycoproteins, many of which represented low abundance secreted and extracellular proteins.…”
Section: Introductionmentioning
confidence: 99%